Efecto del aceite esencial de aloysia triphylla en íleon aislado de cavia porcellus - Pérez Robles, Veronika Nohely (2014)
The present study aimed to determine the spasmolytic effect of Aloysia triphylla essential oil on isolated ileum Cavys type 2. The concentration of the essential oil used was 0.3%, at doses of 0.1 mL and 0.2 mL, were used 8 specimens were divided into two groups : spontaneous and spasmogen, the patterns used were atropine and nifedipine. These isolated organs were stimulated to contract by acetylcholine and potassium chloride. The results were that the essential oil 0.3% (0.2 mL and 0.1 mL) reduced the amplitude of the spontaneous motility similar to atropine and nifedipine, a the frequency difference at the doses mentioned not generate similar effect patterns. Motility induced by spasmogens was obtained 0.2 mL dose, the amplitude and frequency decrease reached similar at the patterns. This observed effect is due to the presence of essential oils, flavonoids and tannins